Quantification and Characterization of Urban Solid Waste and Its Ecological Accounting in Manali City of Hilly Region - Nikita; Aggarwal, R. K.; Bhardwaj, S. K.; Brahmi, M. K. (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted to quantify and characterize the urban solid waste and its ecological accounting in Manali town of Himachal Pradesh during 2020–21. Manali municipality is divided into 7 wards with a population of 8,095. 15 residential households, 8 commercial establishments, and 2 government/semi-government institutes were considered in selected 7 wards. The present study concluded that the MSW generation was higher in summer than winter and out of which biodegradable waste was generated higher than non-biodegradable. The domestic sector contributes the highest waste from different wards. In winter, 132.65 kg of MSW was generated from hotels and restaurants, 85.12 kg from dhabas, 52.54 kg from shops, 21.07 from offices and 6.16 kg from schools. During summer, 164.6 kg of MSW was generated from hotels and restaurants, 58.23 kg from dhabas, 45.22 kg from shops, 16.47 kg from offices and 7.03 kg from schools from different sectors. The urban solid waste of Manali contained 241.31 kg of biodegradable waste and 28.64 kg of non-biodegradable during winter and during summer it contained 262.70 kg of biodegradable and 28.54 kg of non-biodegradable waste. Presently, the 1.47 ha land is required for the disposal of urban solid waste in Manali town. The per capita ecological footprint was found to be 0.000742 gha during winter and during summer the per capita total ecological footprint was 0.00147 gha. The production of bio-compost from biodegradable waste could be important to reduce biodegradable waste.